Alprazolam and Zolpidem in Skeletal Tissue of Decomposed Body Confirms Exposure. Issue 2 (21st August 2018) - Orfanidis, Amvrosios; Gika, Helen; Zaggelidou, Eleni; Mastrogianni, Orthodoxia; Raikos, Nikolaos
Abstract: In several medico‐legal cases, bone samples analysis may provide the only source of toxicological information. This case study reports the analysis of a human bone specimen, belonging to a 46‐year‐old man, found 3 months after his death due to cervical–thoracic injuries in a motorcycle accident. Bone specimen was the only available material for toxicological analysis, among few skull hair and rotten skin. Analysis was performed by a newly developed and validated ultra‐high‐pressure liquid chromatography–mass spectrometry/mass spectrometry (UHPLC‐MS/MS) method, following simple and efficient sample pretreatment. The results were in accordance with the man's medical record: Alprazolam and zolpidem were found at 2.2 and 5.4 ng/g of bone, respectively. Both these drugs were prescribed to the deceased.